Renal Length, packed cell volume and biochemical parameters in subjects with chronic renal failure: a preliminary report (2006)
The constellation of laboratory and imaging findings that distinguish progressive chronic kidney disease (CKD) from acute renal failure are bilaterally small kidneys, elevated PTH, creatol, carbamylated haemoglobin levels, anaemia, hyperphosphataemia and hypocalcemia with elevated parathyroid hormone levels, and a urinary sediments that reveal proteinuria and broad casts. There has been a documented significant correlation between renal legth and GFR, but, the relationship between length and other ureamic and biochemical parameters is still unclear. This study assessed the relationship between renal length and serum biochemistry among chronic renal failure and patients seen at the University College Hospital, Ibadan. Patients withchronic renal failure who presented for the first time in predialytic phase were recruited.Renal ultrasound was used to assess renal length and based on this subjects were classified into those with shrunken kidneys and those with normal kidneys. Blood chemistry including PCV, serum urea and creatinine were performed. Creatinine clearance was calculated using Gault and Cockroft equation. The data were processed using the Statistical Package for the Social Sciences (SPSS) by comparing the means of biochemical parameters of the two groups. Twenty-one patients completed the study; there were 14males and 7 females with age range between 24-72 years, means age of 44.2 (15.4SD) years. Thriteen (61.9%) of them haad kidney length in the abnormal rannge (less than 9cm). No patients had enlarged kidneys. Majority of the patients in this study had bilateral shrunken kidneys but there were no correlations between kidney length and serum creatinine, urea, PCV and creatinine clearance.